2011
DOI: 10.1039/c1em10131e
|View full text |Cite
|
Sign up to set email alerts
|

Global climate change and contaminants—an overview of opportunities and priorities for modelling the potential implications for long-term human exposure to organic compounds in the Arctic

Abstract: This overview seeks to provide context and insight into the relative importance of different aspects related to global climate change for the exposure of Northern residents to organic contaminants. A key objective is to identify, from the perspective of researchers engaged in contaminant fate, transport and bioaccumulation modelling, the most useful research questions with respect to projecting the long-term trends in human exposure. Monitoring studies, modelling results, the magnitude of projected changes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 147 publications
3
73
0
Order By: Relevance
“…Sedimentation rates are within a factor 1.5 in the Arkona Basin and Baltic Proper and can thus not explain the differences in contaminant concentrations. One hypothesis that at least partly may account for the elevated concentrations in the Baltic Proper is that the settling organic matter in the Baltic Proper mainly consists of "fresh" autotrophic organic matter, which may have a higher fugacity capacity compared to "old" and terrestrial organic matter (Armitage et al, 2011). This would imply a higher ratio of organic contaminants to organic carbon in the Baltic Proper compared to e.g., the Arkona Basin where the settling organic matter may consist of a higher proportion of terrestrial organic carbon.…”
Section: Spatial Trends In Surface Sedimentsmentioning
confidence: 99%
“…Sedimentation rates are within a factor 1.5 in the Arkona Basin and Baltic Proper and can thus not explain the differences in contaminant concentrations. One hypothesis that at least partly may account for the elevated concentrations in the Baltic Proper is that the settling organic matter in the Baltic Proper mainly consists of "fresh" autotrophic organic matter, which may have a higher fugacity capacity compared to "old" and terrestrial organic matter (Armitage et al, 2011). This would imply a higher ratio of organic contaminants to organic carbon in the Baltic Proper compared to e.g., the Arkona Basin where the settling organic matter may consist of a higher proportion of terrestrial organic carbon.…”
Section: Spatial Trends In Surface Sedimentsmentioning
confidence: 99%
“…Fluctuations of many POPs on interannual or longer timescales, however, have been observed in POP time series collected from arctic monitoring stations. The longterm trends of POPs in the Arctic have been attributed to the changes in their primary emissions, use patterns, retreating sea ice, degradation, and other complex natural and anthropogenic activities (Macdonald et al, 2005; UNEP/AMAP, 2010; Armitage et al, 2011;Kallenborn et al, 2012). The fluctuations of monitored POP atmospheric concentrations have been also associated with interannual climate change at several POP monitoring sites where the longest atmospheric monitoring programs have been operated, notably the Great Lakes region and the Arctic (Ma et al, 2004a;MacLeod et al, 2005;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of whether currently available POP observational data sets are long enough to address climate change influence on their environmental fate. Several recent modeling investigations and sensitivity analysis to the long-term trend of PCBs and α-HCH in the 20th and 21st centuries suggested that the longterm trends of these POPs were associated more strongly with changes in their emissions and physical-chemical properties, whereas climate change signals were weaker in observed POP time series (Wöhrnschimmel et al, 2013;Armitage et al, 2011;Gouin et al, 2013;Li, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The fate and transport of chemicals in the natural environment will also change in the future. Rising temperatures will increase rates of volatilization and thereby the long-range transport of POPs (Armitage et al 2011) and local exposure to pesticides (Boxall et al 2009). Climate-induced changes in hydrological cycles and regimes will change how contaminants are transported into the aquatic environment, as well as the dilution potential of rivers and streams.…”
Section: Waterborne Diseasementioning
confidence: 99%